Dilma: mãe ou madrasta? Metáforas conceptuais que categorizam a presidente em charges - Ferreira, Barbara Cabral (2015)
Metaphors are present in our day to day. They can be found in all aspects of life. In the area of politics, Lakoff (1995; 2002; 2008a), Lakoff and Wehling (2012) and Kovecses (2000) show that our first encounter with the concept of government happens in the family environment. The primary INSTITUTION AS FAMILY metaphor comes from this experience, and promotes the insurgency of the sub-metaphors THE NATION IS A FAMILY, THE PRESIDENT/ GOVERNMENT IS A PARENT, THE CITIZENS/ OTHER MEMBERS OF THE GOVERNEMENT ARE CHILDREN. The NATION AS FAMILY metaphor is associated with the idea of morality. The idea of morality results in different views of Family, and as a result, what the Nation/ government is. This research‘s goal is to analyze if the PRESIDENT AS PARENT metaphor applies in the Brazilian context regarding the president Dilma. We began with the hypotheses that Dilma is seen as a mother figure, therefore, we tried to identify, based on the models proposed by the previously mentioned authors, how the presidente-mom is categorized. The theoretical foundation for this research is the theory of Idealized Cognitive Models (Lakoff, 1987), the Conceptual Metaphor Theory developed by Lakoff (1993; 2008); Reddy (1993), Lakoff and Johnson (1999; 2002 [1980]; 2003), Ortony (1993), Cameron (2003), Sardinha (2007), among other researchers; Kovecses (2000; 2005) and Yu (2008) studies on metaphor and culture and the relation between metaphor and politics, and metaphor and ideology, according to Goatly (2007) and Charteris-Black (2005). The Corpus is made up of political cartoons published from 2010 to 2014. As a result of this regard, the hypotheses that Dilma is seen as a mother figure has been confirmed. We observed in the corpus that she is categorized either as a nurturant mother, the father´s wife, and mainly as the evil stepmother. We also observed that a patriarchalist, sexist and convervatist political-ideological point of view is prevalent in the cartoons.